2021
DOI: 10.3390/plants10040647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mammalian Two-Pore Channel Inhibitors on Long-Distance Electrical Signals in the Characean Macroalga Nitellopsis obtusa and the Early Terrestrial Liverwort Marchantia polymorpha

Abstract: Inhibitors of human two-pore channels (TPC1 and TPC2), i.e., verapamil, tetrandrine, and NED-19, are promising medicines used in treatment of serious diseases. In the present study, the impact of these substances on action potentials (APs) and vacuolar channel activity was examined in the aquatic characean algae Nitellopsis obtusa and in the terrestrial liverwort Marchantia polymorpha. In both plant species, verapamil (20–300 µM) caused reduction of AP amplitudes, indicating impaired Ca2+ transport. In N. obtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…An AP is a short-term depolarization spike including two phases (depolarization and repolarization) [ 28 , 35 , 77 , 78 ] which is induced by non-damaging irritations (e.g., electrical current [ 79 , 80 , 81 , 82 , 83 ], cooling [ 41 , 79 , 84 ], touch [ 85 , 86 , 87 ], initiation or termination of illumination [ 88 , 89 ]). The generation of an AP is in accordance with the “all-or-none law” [ 8 , 28 , 35 ]; it is a self-propagating signal with typical velocities ranging from 1 mm s −1 to 10 cm s −1 in different plants [ 8 , 38 , 77 , 80 ].…”
Section: Electrical Signals In Plants: Types and Mechanismsmentioning
confidence: 99%
“…An AP is a short-term depolarization spike including two phases (depolarization and repolarization) [ 28 , 35 , 77 , 78 ] which is induced by non-damaging irritations (e.g., electrical current [ 79 , 80 , 81 , 82 , 83 ], cooling [ 41 , 79 , 84 ], touch [ 85 , 86 , 87 ], initiation or termination of illumination [ 88 , 89 ]). The generation of an AP is in accordance with the “all-or-none law” [ 8 , 28 , 35 ]; it is a self-propagating signal with typical velocities ranging from 1 mm s −1 to 10 cm s −1 in different plants [ 8 , 38 , 77 , 80 ].…”
Section: Electrical Signals In Plants: Types and Mechanismsmentioning
confidence: 99%
“… 133 A recent study in Nitellopsis obtusa and Marchantia polymorpha has shown that inhibitors of human two-pore channels alter resting potential, action potential amplitudes and the duration of action potential repolarization by affecting channels. 134 In addition to having a short-lasting depolarisation of the action potential, animals and plants both have signals based on prolonged depolarisation. In animals, a prolonged depolarisation signal is the plateau potential, 135 , 136 and in plants it is the variation potential.…”
Section: The Definition Of a Nervous Systemmentioning
confidence: 99%
“… 133 A recent study in Nitellopsis obtusa and Marchantia polymorpha has shown that inhibitors of human two-pore channels alter resting potential, action potential amplitudes and the duration of action potential repolarization by affecting channels. 134 …”
Section: The Definition Of a Nervous Systemmentioning
confidence: 99%
“…In Arabidopsis, AtTPC1 forms the slow vacuolar (SV) channel [3]. Nevertheless, SV channels have also been characterized in non-vascular mosses and liverworts [39][40][41][42]. Marchantia polymorpha is a representative of liverworts, which are regarded as pioneer plants that colonized the land around 500 million years ago.…”
Section: Discussionmentioning
confidence: 99%